Pemberian Nugget Tahu Daun Kelor Berpengaruh Terhadap Kenaikan Berat Badan Balita - Rahmawati, Afifah; Pramono, Joko Sapto; Suryani, Heni (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2024)
Nutrition is a crucial element in food that plays a vital role in ensuring an individual's growth and development. Malnutrition is a common nutritional problem that affects children below the age of five. It occurs when the body lacks or has an imbalance of vital nutrients necessary for growth, cognitive development, and overall well-being. The preliminary study conducted at the Teratak Village Community Health Center found that some toddlers had a body weight that was below the recommended weight according to the age indicator in the KMS. The study had a pre-experimental design with a one-group pre-and-post-test approach. A total of 20 toddlers aged between 24 to 60 months who were below the yellow line (BGK) and the red line (BGM) on the KMS graph were sampled during the weighing period between October 2022 – March 2023. The paired sample t-test method was used to analyze the changes in body weight. The study found that 16 toddlers experienced weight gain while two others did not show any increase in weight after the intervention. The statistical test resulted in a p-value of 0.000 (< α = 0.05), demonstrating that providing Moringa leaf tofu nuggets had a significant effect on the weight gain of toddlers. Providing additional food with tofu nuggets and Moringa leaves can increase toddlers' weight, with 50 grams of nuggets containing an additional protein intake of 5.65 grams.